PENGARUH KEPEMIMPINAN, KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Pada Kospin JASA Cabang di Semarang) - Yulia Anggraini, 13.05.51.0021 (Students Journal of Economic and Management, 2017)
This study aims to determine and analyze the effect of leadership, competence, and organizational culture on employee performance at Kospin JASA Branch in Semarang. This study also aims to determine jointly the effect of the three independent variables to the dependent variable and to determine which variables are the most dominant influence among the three independent variables to the dependent variable. This research uses qualitative research, the sample used is 50 respondents, using census technique so that all respondents are taken as research sample and collecting using questionnaires with Likert scale. Relationship and effect between variables is explained by using multiple linier regression analysis method. Keywords: Leadership, competence, organizational culture and employee performance.